Counting hard-to-count populations: the network scale-up method for public health. (23rd November 2010) - Bernard, H Russell; Hallett, Tim; Iovita, Alexandrina; Johnsen, Eugene C; Lyerla, Rob; McCarty, Christopher; Mahy, Mary; Salganik, Matthew J; Saliuk, Tetiana; Scutelniciuc, Otilia; Shelley, Gene A; Sirinirund, Petchsri; et al.
Abstract : Estimating sizes of hidden or hard-to-reach populations is an important problem in public health. For example, estimates of the sizes of populations at highest risk for HIV and AIDS are needed for designing, evaluating and allocating funding for treatment and prevention programmes. A promising approach to size estimation, relatively new to public health, is the network scale-up method (NSUM), involving two steps: estimating the personal network size of the members of a random sample of a total population and, with this information, estimating the number of members of a hidden subpopulation of the total population. We describe the method, including two approaches to estimating personal network sizes (summation and known population). We discuss the strengths and weaknesses of each approach and provide examples of international applications of the NSUM in public health. We conclude with recommendations for future research and evaluation.